2017
DOI: 10.1371/journal.pone.0187128
|View full text |Cite
|
Sign up to set email alerts
|

Differential host mortality explains the effect of high temperature on the prevalence of a marine pathogen

Abstract: Infectious diseases threaten marine populations, and the extent of their impacts is often assessed by prevalence of infection (the proportion of infected individuals). Changes in prevalence are often attributed to altered rates of transmission, although the rates of birth, recovery, and mortality also determine prevalence. The parasitic dinoflagellate Hematodinium perezi causes a severe, often fatal disease in blue crabs. It has been speculated that decreases in prevalence associated with high temperatures res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
2
1
Order By: Relevance
“…This is in contrast with recent studies from Louisiana, in Fig. 3 which H. perezi DNA was detected in blue crab megalopae (Sullivan et al 2016, Sullivan & Neigel 2017. Although there are ecosystem differences between the Delmarva Peninsula and the Gulf of Mexico, there is a potential confounding factor in the study by Sullivan et al (2016) and their later analyses.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This is in contrast with recent studies from Louisiana, in Fig. 3 which H. perezi DNA was detected in blue crab megalopae (Sullivan et al 2016, Sullivan & Neigel 2017. Although there are ecosystem differences between the Delmarva Peninsula and the Gulf of Mexico, there is a potential confounding factor in the study by Sullivan et al (2016) and their later analyses.…”
Section: Discussioncontrasting
confidence: 75%
“…Little is known about whether the parasite can infect larval stages. Sullivan et al (2016) and Sullivan & Neigel (2017) detected Hematodinium DNA associated with blue crab megalopae collected from inshore locations in Louisiana, but their studies did not demonstrate whether the positive PCR assays were associated with internal infections.…”
Section: Introductionmentioning
confidence: 94%
“…This observation is similar to the Hematodinium perezi−C. sapidus pathosystem, in which a negative relationship was found between high water temperature and the prevalence of H. perezi infections in C. sapidus megalopae because higher temperature caused faster mortality of infected crabs (Sullivan & Neigel 2017). We found that the load of CsRV1 RNA was consistently lower in warmer latitudes (Table S3), which could indicate that crabs with higher CsRV1 loads do not live long enough to be sampled.…”
Section: High Temperaturesupporting
confidence: 82%
“…To better understand the various influences on this complex pathosystem, it is necessary to combine field observations with experimental data as suggested by Sullivan & Neigel (2017). Laboratory experiments are needed to test the effect of temperature on the progression of CsRV1 infections and resulting mortality rates across a wide temperature gradient representing temperate to tropical environments.…”
Section: Concluding Remarks and Next Stepsmentioning
confidence: 99%